Politics in Guimaras the emergence and resilience of factions, 1932-present - De Asis, Candice Lauren Tuason
This politico - historical study identifies the factors that contribute to the emergence and resilience of politcal factions in Guimaras. The study was conducted with the use of primary and secondary sources of information and interviews. The history of politics in Guimaras was accounted starting from Spanish colonial regime up to the present. The factors that contribute to the emergence of factions were brought about by the provincehood of Guimaras that gave away for local political groups to evolve and compete during elections with minimal or complete absence of interference from the Province of Iloilo, the differences of principles by members of the same faction that enable them to transfer to the other political camp, the interest of members, and their search for political exposure. However, some individuals stay in the faction due to their loyalty, friendship, social relationship, unity in principles, political and economic security, the need for mobilizing support, and also political exposure. Factionalism affects the policies and decisions of the provincial government of Guimaras in both positive and negative ways thus, results to the development and underdevelopment of the province. In the course of the study, the researcher concludes that there is a high degree of factionalism in the province thus, creating a contestual atmosphere in local politics.